1962
DOI: 10.1161/01.cir.25.5.798
|View full text |Cite
|
Sign up to set email alerts
|

Hourly Changes in Serum Cholesterol Concentration

Abstract: Further evidence has been obtained to indicate that the concentration of serum cholesterol can vary widely during the course of a few hours in certain individuals. The data are consistent with a hypothesis that changes in the concentration of serum cholesterol may relate to the anticipation of an event as well as to the event itself. Similarity in the hourly variation in serum cholesterol concentration occurring among eight carefully selected subjects, during control as well as during test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1963
1963
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Several investigators have reported that psychic stress and the anticipation of psychic stress can cause an elevation in serum cholesterol( [10][11][12][13]. The absence of significant differences between the 2 test groups suggests that, under the conditions of this experiment, restraint alone caused as much stress for the squirrel monkey as restraint plus decisionmaking.…”
mentioning
confidence: 59%
“…Several investigators have reported that psychic stress and the anticipation of psychic stress can cause an elevation in serum cholesterol( [10][11][12][13]. The absence of significant differences between the 2 test groups suggests that, under the conditions of this experiment, restraint alone caused as much stress for the squirrel monkey as restraint plus decisionmaking.…”
mentioning
confidence: 59%
“…Cold water immersion can lead to an increase in cholesterol (15), and interestingly, even the anticipation of being placed in the cold can lead to a 65% increase in cholesterol (58). Similarly, the hypnotic suggestion of stresses not actually present is also sufficient to affect lipids.…”
Section: Anticipation and Hypnosismentioning
confidence: 99%
“…absence of any baseline level of cholesterol concentration, man's serum cholesterol level for any given period in his life has been found to be related to certain psychologic moods and feelings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). For example, it has been shown that depressed mental patients demonstrate elevated serum cholesterol levels (4,5).…”
mentioning
confidence: 99%
“…When his subjects demonstrated low serum cholesterol levels, they reported that they had been recently relaxed, comfortable and secure (9). Hence, a consensus of available data indicates that human psychologic moods and feelings of aggression, hostility (generally repressed), competitiveness, time urgency, independence, self-criticism, guilt, depression and of being overburdened are associated with high serum cholesterol levels, while mood and feeling states of security, comfort and relaxation are associated with low serum cholesterol levels (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In studies of subjects with coronary heart disease, where most of these persons had relatively high serum cholesterol levels, the subjects were described as being aggressive, competitive and hardworking individuals who frequently felt their lives to be characterized by rushing against time deadlines (7).…”
mentioning
confidence: 99%